La descentralización educativa en el Perú - Neida Alvarez Laveriano (Pontificia Universidad Católica del Perú, 2010)
This essay introduces the educational decentralization as an important issue of the global public reform that become in different kinds of relationship between the State and the civil society. To precise this subject, this article develops conceptual distinctions among concepts close to the decentralization area. In addition,advantages and disadvantages of the decentralization are mentioned. At the last, the author analyzes the background and legislation of the Peruvian educational decentralization.